2015
DOI: 10.1111/imb.12185
|View full text |Cite
|
Sign up to set email alerts
|

Ecdysone receptor isoform‐B mediates soluble trehalase expression to regulate growth and development in the mirid bug, Apolygus lucorum (Meyer‐Dür)

Abstract: Ecdysone receptor (EcR) is the hormonal receptor of ecdysteroids and strictly regulates growth and development in insects. However, the action mechanism of EcR is not very clear. In this study, the cDNA of EcR isoform-B was cloned from Apolygus lucorum (AlEcR-B) and its expression profile was investigated. We reduced AlEcR-B mRNA expression using systemic RNA interference in vivo, and obtained knockdown specimens. Examination of these specimens indicated that AlEcR-B is required for nymphal survival, and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Thus, under these circumstances, trehalose cannot be converted into glucose to provide energy and substrate for chitin synthesis for pupal-adult development, which could be the reason of the delay in adult emergence that was observed in CucB- treated A. pernyi . This observation is in agreement with a previous study, in which the knockdown of EcR was found to reduce the soluble trehalase activity, in turn preventing the normal growth and development of A. lucorum ( Tan et al 2015 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Thus, under these circumstances, trehalose cannot be converted into glucose to provide energy and substrate for chitin synthesis for pupal-adult development, which could be the reason of the delay in adult emergence that was observed in CucB- treated A. pernyi . This observation is in agreement with a previous study, in which the knockdown of EcR was found to reduce the soluble trehalase activity, in turn preventing the normal growth and development of A. lucorum ( Tan et al 2015 ).…”
Section: Discussionsupporting
confidence: 94%
“…Consistent with our results, the expression levels of LdTre-1a , LdTre-1b , and LdTre-2 were significantly reduced after LdEcR gene in Leptinotarsa decemlineata (Coleoptera: Chrysomelidae) third-instar larvae was knocked down ( Shi et al 2016 ). Also, mRNA and protein levels of AlTre1 decreased after the injection of AlEcRB -specific siRNA, which resulted in decreased soluble trehalase activity and increased trehalose content in the nymphs of A. lucorum ( Tan et al 2015 ). In the present study, neither the treatment with ApEcRB1 -specific RNAi nor with CucB led to the decrease in ApTre-1B expression ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that the mRNA levels of TRE1 increase before insect moulting and after the injection of 20E 21 23 24 . In Apolygus lucorum , ecdsone receptor (EcR) isoform-B mediates the expression of TRE1 expression and regulates growth and development 25 .…”
mentioning
confidence: 99%
“…EcRB mutants having removed both EcRB1 and EcRB2 show defects in larval molting, arresting at the boundaries between the three larval stages (Schubiger et al ., ). Similarly, silencing either EcRA or EcRB1 inhibits growth and increases juvenile mortalities in A. lucorum (Tan et al ., , b).…”
Section: Discussionmentioning
confidence: 99%